A "Feel-Good" Future: Hopes and Class Identities Among Martial Arts Students in China. Issue 6 (July 2019) - Dong, Xuan
This article examines how a group of martial arts students in China make sense of their futures and how their hopes toward a "feel-good" future reveal and affect their perceived class identities. Twelve months of ethnographic fieldwork was conducted in Dengfeng, a county-level city in central China. Dengfeng was home to 48 registered martial arts schools and more than 70, 000 full-time students in 2012. By uncovering the hopes, aspirations, and perceived class identities of people in martial arts schools, this article argues that the process of class-making for these martial arts students results in constantly reorienting their hopes. These hopes often reflect social comparisons with familiar others like parents, friends, and acquaintances.